Epidemiology of Avian Tuberculosis in Selected Districts of Oromia Region, Ethiopia - Tesfaye Debelu; Fufa Abunna; Gezahegne Mamo Kassa; Gobena Ameni (Veterinary Medicine International)
Avian tuberculosis is a growing public health concern and a significant impediment to socioeconomic development, especially in developing countries, where the risk of infection is high. The disease is predominantly caused by Mycobacterium avium belonging to serotypes 1, 2, 3, and 6 (genotypes IS901 and IS1245) and Mycobacterium genavense. It mostly occurs in older birds and immunocompromised individuals due to the greater opportunity for infection with age and host immunity. A cross-sectional study anticipated to generate epidemiological information on avian tuberculosis was carried out from November 2016 to June 2017 at highland areas of Gerar Jarso, Ada’a (midland), and Boset (lowland) districts of Oromia region, Ethiopia. Two hundred seventy-three village chickens comprising local breeds, exotic breeds, and crossbreeds of both sexes were used in the study. Single intradermal avian tuberculin test, postmortem inspection of positive reactors, mycobacteriological culturing, and histopathological examination were used to assess information on the epidemiology of the disease. Subsequently, avian tuberculin test revealed an overall apparent prevalence of 11.4% (31/273) and a specific prevalence of 6.8% (6/88) in the highland, 13.4% (13/97) in the midland, and 13.6% (12/88) in the lowland study districts. Besides, it signified a higher odd of exposure in crossbreeds and females as compared to locals and males. In addition, greater odd of exposure was observed in chickens at mid- and low altitudes as compared to those at the highland. Moreover, 40.9% (9/22) of positive reactor chickens sacrificed for necropsy showed gross pathological lesions. Similarly, histopathological examination revealed a granuloma characterized by central necrosis and peripheral mononuclear lymphocytes. Nevertheless, only 0.02% (2/120) of the cultured tissues had shown colonial growth up to 12 weeks of incubation, and both were seen on sodium pyruvate-enriched Lowenstein–Jensen medium slants. Generally, the study revealed an overall increment of the apparent prevalence of avian tuberculosis with decreasing altitude. Besides, it signified a relative breed and sex variation in the risk of acquiring the disease, with crossbreeds and female chickens having higher odds of exposure.